Propuesta de modelo de asignación de centros de distribución para la empresa león león e hijos S.A.S (2020)
In the present work called PROPOSAL OF ALLOCATION MODELS OF DISTRIBUTION CENTERS FOR THE COMPANY LEÓN LEÓN E HIJOS S.A.S; The use of allocation models for a better functioning of the logistics chain in the distribution-transport area is shown, in addition, this research shows the importance of route optimization to achieve the sustainability of a system. In the course of the last decade, the company has strengthened its distribution processes in road transport, since it has generated economic growth in the Boyacá region and due to the excellence of its service, products are available to the end consumer. ; What can be observed in the logistics service provider is to reduce variables that affect the quality of the process, that is, to reduce the PQRS of customers, improve the delivery times of orders, reduce the NFP or so-called returns, better optimization of the vehicles to meet the demand of each of the routes. For this reason, it is important to carry out a study that covers the times of each of the procedures, to investigate through the collaborators the shortcomings in the distribution that occur in the working day in order to have other solution alternatives, to monitor the process through indicators and finally the application of tools such as a simulation of a distribution center design will contribute to an improvement in times, routing system and distribution organization.